18F-Fluorodeoxyglucose uptake level-based lymph node staging in oropharyngeal squamous cell cancer: role of molecular marker expression on diagnostic outcome - Sadick, Maliha; Weiß, Christel; Hörmann, Karl; Schönberg, Stefan; Sadick, Haneen (Oncology research and treatment, 2015)
Background: A prospective study was performed to assess standard uptake value (SUV)-level based 18F-fluorodeoxyglucose (FDG)-positron emission tomography (PET)/computed tomography (CT) lymph node staging in 33 patients with oropharyngeal squamous cell cancer (OSCC) out of a total of 99 patients with head-and-neck squamous cell cancer (HNSCC) and the role of nodal molecular marker expression in diagnostic outcome prediction. Methods: Preoperative nodal PET/CT staging in 123 lymph nodes was correlated with postoperative lymph node histology, which served as gold standard. Tissue samples were prepared for immunohistochemistry of the excised lymph nodes. Results: The negative and positive predictive values (NPV and PPV) of PET for correct lymph node assessment were 100% and 93%, respectively. There was a significant association between SUVmax and lymph node histology (p < 0.0001) and a significant linear correlation between SUVmax and nodal size (Pearson's correlation coefficient r = 0.61336, p < 0.0001). The molecular marker E-Cadherin was significantly overexpressed in lymph node metastases (p < 0.0001). Benign lymph nodes showed significant 2-fold Bcl2 overexpression (p < 0.0001). However, the molecular marker expression profiles were inhomogeneous and did not allow valuable diagnostic outcome prediction. Conclusions: SUV level-based 18F-FDG-PET/CT lymph node assessment in OSCC still has to be considered as the most established and reliable staging tool. Lymph node molecular marker expression profiles need to be investigated further as they currently do not sufficiently contribute to therapy decision-making.